An Optimized Modal Balancing Approach for a Flexible Rotor Using a Vibration Response While the Rotor Is Speeding Up - Liqing Li; Yuanhang Hou; Shuqian Cao (Shock and Vibration)
The modal balancing method (MBM) is an effective method for reducing the vibration caused by the unbalancing of a rotor. A rotor’s modal parameters, especially its modal shapes, need to be accurately calculated in this method. This paper proposes an optimized modal balancing approach for flexible rotors. The vibration modes of the rotor are first obtained with experimental modal analysis based on the rotor’s response signals while the rotor is speeding up. The rotor balancing strategy is subsequently optimized by the sensitivity analysis of the mode shapes. Orthogonal trial masses are obtained based on the orthogonality of each vibration mode, and the correction masses are finally calculated by using the influence coefficients of the trial masses. An experimental result is shown to demonstrate and validate that the proposed approach is able to achieve superior accuracy compared to the conventional MBM.